2020
DOI: 10.1007/s00432-020-03351-2
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of tryptophan 2,3-dioxygenase inhibition on SK-Mel-28 and HCT-8 cancer cell lines

Abstract: Purpose Indoleamine 2,3-dioxygenase-1 (IDO1) and more recently, tryptophan 2,3-dioxygenase (TDO), are tryptophancatabolizing enzymes with immunoregulatory properties in cancer. IDO1 is more expressed than TDO in many tumours including melanomas; however, IDO inhibitors did not give expected results in clinical trials, highlighting the need to consider TDO. We aimed to characterize both TDO expression and function in a melanoma cell line, named SK-Mel-28, with the purpose to compare it with a colon cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Because TDO is involved in the regulation of SK-Mel-28 growth [ 24 ], and since dex induced TDO up-regulation, we then wished to determine whether dex stimulates SK-Mel-28 proliferation via TDO. Our results show that dex significantly and concentration-dependently increased SK-Mel-28 proliferation ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because TDO is involved in the regulation of SK-Mel-28 growth [ 24 ], and since dex induced TDO up-regulation, we then wished to determine whether dex stimulates SK-Mel-28 proliferation via TDO. Our results show that dex significantly and concentration-dependently increased SK-Mel-28 proliferation ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…To delineate the mechanisms underlying the proliferative effect of dex, cells were pretreated for 15 min with 680C91 (40 μM), a selective TDO inhibitor, followed by dex (25 μM). Interestingly, 680C91 significantly hampered cell proliferation by 41.2 ± 7.1%, without affecting either cell viability [ 24 ] or cell duplication in response to FGF2 ( Figure 5 C). Furthermore, inhibition of IDO1 with 1-MT or epacadostat, a newer IDO1 inhibitor, potentiated dex-induced cell proliferation ( Figure 5 D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that phosphorylation of AKT and ERK controls apoptosis [ 33 ]. Interestingly, a recently developed TDO2 inhibitor has shown an ability to impair cell proliferation by inducing apoptosis and cell cycle arrest [ 34 ]. These data suggest that TDO2 may take part in the activation of EGFR and promote tumor growth in RCC.…”
Section: Discussionmentioning
confidence: 99%